Protocol for obtaining Cedrela odorata L. plants through tissue culture (Research, Society and Development, 2020)
The work aimed to develop a basic protocol for micropropagation of Cedrela odorata L. plants from seedlings germinated in vitro. The experiments were conducted at the Embrapa Amazônia Oriental Genetic Resources and Biotechnology laboratory. For the disinfestation of seeds, sodium hypochlorite solution was tested at 0; 1.0; 1.5 and 2.0% for 10, 15 and 20 minutes. For budding induction in MS medium, 5 concentrations of BAP and 2 types of segments were tested and rooting was used 0; 1.0; 1.5; 2.0 and 2.5 mg.L-1 of ANA. The design used was completely randomized or in a factorial arrangement according to the treatments analyzed. The data obtained in the different experiments were subjected to analysis of variance and the means compared by the Tukey test at 5% probability. The results showed that the use of 2.0% sodium hypochlorite for 15 minutes showed the lowest percentage of contamination of the seeds. Treatment with 1 mg. L-1 of BAP promoted the largest number and length of shoots in apical segments and with the addition of 2 g.L-1 of sucrose induced the appearance of shoots in stem segments. The largest number and length of root / explant was obtained with 1 mg. ANA L-1. It is possible to obtain a complete Cedrella odorata plant from disinfected seeds in 2.0% sodium hypochlorite solution, and the use of 1 mg. L-1 of BAP and ANA for budding induction and rooting, respectively.